TRANSDUCERS 2007 - 2007 International Solid-State Sensors, Actuators and Microsystems Conference 2007
DOI: 10.1109/sensor.2007.4300486
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Lateral Field Excited Acoustic Wave Device as a New Sensor Principle in Biointerface Analysis

Abstract: AT-cut quartz crystals have been excited by applying a lateral electric field in the plane of the disk. Deposition of self-assembled monolayers proves the expected sensitivity of the sensor to small mass changes. When subjected to a liquid acoustic load the sensor exhibits an extremely high sensitivity to permittivity and conductivity of the liquid. In combination with an additional artificial interface layer, the influence on the resonance will be discussed in terms of reorganization of the electric field dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Even more pronounced results have been obtained in our own experiments with electrolytic solutions [9,10]. Moreover, it could be shown that a remarkable sensor response can be generated in the absence of any mechanical (liquid) load on top of the sensor surface simply by placing a shielding electrode, connected to ground potential, in close proximity to the bare quartz surface.…”
Section: Motivationsupporting
confidence: 54%
“…Even more pronounced results have been obtained in our own experiments with electrolytic solutions [9,10]. Moreover, it could be shown that a remarkable sensor response can be generated in the absence of any mechanical (liquid) load on top of the sensor surface simply by placing a shielding electrode, connected to ground potential, in close proximity to the bare quartz surface.…”
Section: Motivationsupporting
confidence: 54%
“…The variation pattern also matched the numbers provided in Figure 8 c, which were the conductivity values measured using a portable conductivity meter. The conductivity value had a good linear relationship with the frequency shift, which was also consistent with the linear relationship exhibited by the QCM in the low concentration conductivity solution in the literature [ 16 , 36 ]. Therefore, this experiment also proved that the temperature effect had a considerable influence on the measurement of the electrical properties of QCM, and it was not possible to simply neglect the influence of the liquid viscosity and density during the measurement in the liquid.…”
Section: Resultssupporting
confidence: 89%
“…This kind of electrode structure enables the electrical field to penetrate into the liquid. Therefore, LFE-QCM has extremely high sensitivity to electrical properties in the liquid, and the mechanical properties similar to the TFE sensor [ 15 , 16 , 17 , 18 ]. At present, many studies have been completed on LFE-QCM, which has been shown to have many advantages over traditional QCM in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, York et al 15) examined the quartz sensor in biochemical sensing and found LFE has matched or even further exceeded the QCM in the sensor parameters of reproducibility, reusability, response time, and stability. In 2007, Hempel et al 16) also presented LFE bio-sensors and assumed that liquid on the sensing surface acts as a virtual electrode to the metallic LFE electrode. In 2011, Chen and Liu 17) first presented the LFE sensor in gas sensing by finite element method, which provides the concept of this work.…”
Section: Introductionmentioning
confidence: 99%